Explanatory remark on differences between a position paper and an empirical paper - Adeoye, Moses Adeleke (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2023)
An accessible explanation of academic writing differences between a position paper and an empirical paper for graduate students’ writing approach. The purpose is for graduate scholars who want to use these articles for basic knowledge and fundamental ideas. It can also be used as a textbook or reference. The paper revealed information regarding academic writing differences between position papers, empirical papers and authenticate benefits. Both position papers and empirical papers involve research and analysis but the main difference is that position papers present a specific stance or argument while empirical papers present objective data and research findings. It was concluded that a position paper and an empirical paper focus on argumentation persuasion versus original research create a new body of knowledge scientifically.